Some fixed point theorems in n-normed spaces - Hanan Sabah Lazam; Salman Abed, Salwa (Al-Qadisiyah Journal of Pure Science, 2020)
In this article, we recall the definition of a real n-normed space and some basic properties. fixed point theorems for types of Kannan, Chatterge, Zamfirescu, -Weak contraction and - (,)-Weak contraction mappings in Banach spaces.